Motherhood pay gap and employment - Otto, Paulina Clara (2022)
This work project investigates to what extent the motherhood pay gap has maturedover35 years. Child birth often leads mothers to pause their employment. Consequently, mothers’ wages and employment opportunities are often impacted. The analysis highlights the wage gap issues, employment differences and opportunities between childless women and mothers with various years of maternity leaves. The reviewed data from the German SOEP panel set high lights that throughout the years, the motherhood pay gap has not decreased .In Germany, opportunities for women have not significantly changed and childless women continuously have beneficial prospects in the labor market compared to mothers.